TARI BALANSE MADAM PADA MASTARAKAT NIAS DI PADANG SUMATERA BARAT: KAJIAN KOMPARASI BENTUK - Novina Yeni Fatrina (Dewa Ruci: Jurnal Pengkajian dan Penciptaan Seni, 2009)
Balanse Madam dance is traditional dance of Nias Padang society.  Balanse Madam dance  belongs to social dance with the married dancer.   Balanse Madam dance performance  is  accompanied with western music instrument such as drum set, accordion, violin,  guitar, tambourine, drum and tambour.   Balanse Madam dance performance in the  customary event in 2007, was different from the one in 1994. To raise the phenomenon  in  a scientific writing, therefore descriptive qualitative research with observation  technique, interview by means of analysis interaction and data analysis using analysis  interpretation would be used.   It is found that there were form changes in the Balanse  Madam performance, including unmar- ried dancer, dance accompanied by single-organ  and some different term of com- mand from commander.   The differences might be used  by discontinuous inherit- ance system. Keywords: Balanse Madam, comparation, form.